Pengaruh Budaya Organisasi dan Lingkungan Kerja terhadap Kinerja Karyawan: Studi Kasus PT. Indomarco Prismatama Cabang Cakung Timur - Rahayu, Annisa; Ilyas, Yusri; Sekarini, Ratih Ayu (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This research aims to determine the influence of organizational culture and work environment on employee performance at PT. Indomarco Pritmatama East Cakung Branch. This type of research uses quantitative methods. The data collection technique uses a questionnaire distribution technique. The popilation of this study was 40 respondents. This research used 40 saturated samples. For data analysis using classical assumption tests, multiple regression analysis and hypothesis testing. The adjusted R Square value (coefficient of determination) is 0.799, which means that the influence of the independent variable on the dependent variable is very strong, namely 79% and the remaining 21% is influenced by other variables outside the regression model that the author wrote studied. Based on the results of tests carried out, it shows that simultaneously Organizational Culture and Work Environment have a significant effect on PT Employee Performance. Indomarco Prismatama East Cakung Branch. Meanwhile, partially Organizational Culture (X1) has a positive and significant effect on Employee Performance. Work Environment (X2) has a positive and significant influence on employee performance.